SPECTRAL PARAMETERS OF THE GROUND MOTIONS IN CAUCASIAN SEISMOGENIC ZONES - Sokolov V.Yu. (My University, 1998)
A collection of ground-motion recordings including accelerograms of the mainshock of the 7 December 1988, Spitak earthquake (M = 6.9, Northern Armenia) has been obtained during the 1988 to 1990 strong-ground-motion network operation. This region of the Caucasus still has a poor database for strong-ground-motion prediction, but the data studied here form a basis for source scaling and attenuation relation study. The results show that the acceleration spectra of shear waves recorded at rock sites can be modeled accurately by the Brune source model using a stress parameter of 50 to 100 bar (Spitak area) and 200 bar (events to the North from the Spitak area), and cutoff frequency f(max) = 7 to 10 Hz. The anelastic attenuation Q of spectral amplitudes with distance may be described by the form published by Boore (1987) Q = 29.4 [1 + (f/0.3)2.9]/(f/0.3)2 up to distances R = 70 km. The comparison of modeled bedrock spectra with observed data (registered at shallow soil deposits) allowed the author to estimate the local site response in terms of frequency-dependent amplification functions. The generalized regional amplification function was used to predict ground motion in conditions of shallow soils. Stochastic simulation of ground motions (peak ground acceleration and response spectra) using the obtained models of source spectra and attenuation shows good agreement with observed data.